PENANAMAN POHON PELINDUNG SEBAGAI UPAYA PELESTARIAN LINGKUNGAN DAN MENCEGAH BANJIR DI KAWASAN BENDUNGAN MENINTING DESA BUKIT TINGGI KECAMATAN LINGSAR - LOMBOK BARAT - Dewi Rispawati; Lale Puspita Kembang (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
This Community Service is themed "Planting Shade Trees as an Effort to Preserve the Environment and Prevent Flooding in the Meninting Dam Area, Bukit Tinggi Village - Lingsar District, West Lombok". The purpose of this Community Service is to preserve the environment and prevent flooding around the Meninting Dam area, Bukit Tinggi Village - Lingsar District, West Lombok Regency. In this Community Service, three methods are used in its implementation, namely (1) Preparation and Socialization of Community Service Activities Planting Shade Trees, (2) Implementation of Community Service Activities Planting Shade Trees and (3) Monitoring and Evaluation of Community Service Activity Results Planting Shade Trees. The results of Community Service Activities in the Meninting Dam area, Bukit Tinggi Village, Lingsar District, West Lombok are very useful for environmental preservation so that the environment remains sustainable, beautiful and green and prevents flooding around the Meninting Dam area, Bukit Tinggi Village, Lingsar District, West Lombok Regency which is prone to flooding when the rainy season comes. In tree planting, around 100 shade tree seedlings were planted in the Meninting Dam area, Bukit Tinggi Village, Lingsar District, West Lombok Regency. With this planting of shade tree, it is hoped that local residents can care for and maintain the planted tree seedlings so that the environment becomes sustainable, beautiful and green and prevents flooding.